Análise de citações de teses como apoio à tomada de decisão no desenvolvimento de coleções de bibliotecas universitárias - Ana Maria Mattos (2008)
The aim of this research is analyze dissertations citations patterns uphold between 1999 and 2007 in the Programa de Pós-Graduação em Administração of Escola de Administração at Universidade Federal do Rio Grande do Sul, and built up indicators to support library`s collection development decision-making. In doing so, we analyzed the kind of bibliographic materials used, his age, the main journals, and thereferences language. The result allows optimize resources` allocation and investment in informational material, establish retrospective collection storage guidelines, determining the core collection journals composition, indicate what language bibliographical materials should be selected in future acquisitions, and prepare for collection cuts due to possible library budget reductions.